PENGGUNAAN CONCRETE FILLED STEEL TUBULAR (CFST) SEBAGAI ELEMEN STRUKTUR JEMBATAN PEJALAN KAKI - Sugeng Riyanto, Wahiddin, Mohamad Zenurianto (Prokons: Jurnal Teknik Sipil, 2018)
The concrete filled steel tubular element (CFST) is a hollow steel profile filled with concrete. The axial capacity of CFST elements is greater than its bending capacity. The CFST element will be used as an element structure of pedestrian arc bridge. In this research, we will analyze the structure of arc bridge with variation of height rasio of arc to span of bridge (y/L) and height ratio of floor elevation to span of bridge (h/L). The ratio value y / L = 1/6, produces a larger axial force while the moment that occurs is very small. While the ratio of h / L = 1/7, it produces minimum axial force on the least element of the arch bridge.           Keywords: concrete filled steel tubular, pedestrian bridge